1989
DOI: 10.1068/p180231
|View full text |Cite
|
Sign up to set email alerts
|

Making Mayhew and Frisby Effortlessly Discriminable

Abstract: Mayhew and Frisby (1978) demonstrated that patterns which differ markedly in their spatial-frequency content may be very hard to discriminate. This they took as evidence against any model which proposes that the processes underlying texture discrimination have direct access to some local piecewise Fourier analysis of the patterns performed by spatial-frequency channels. It is shown that Mayhew and Frisby's patterns can be discriminated easily if their components have been incorporated into a pattern-contingent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Hence, it could be argued that the McCollough effect emerges preattentively, prior to the (attentive) detection of the involved orientations, since to see the aftereffect colors the orientation of the oriented gratings would have to have been detected. found results similar to those of Thompson and Travis (1989) using visual search tasks. They investigated whether aftereffect colors could act like a simple ''feature'' in a visual search task.…”
Section: Attention and The Mccollough Effectsupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, it could be argued that the McCollough effect emerges preattentively, prior to the (attentive) detection of the involved orientations, since to see the aftereffect colors the orientation of the oriented gratings would have to have been detected. found results similar to those of Thompson and Travis (1989) using visual search tasks. They investigated whether aftereffect colors could act like a simple ''feature'' in a visual search task.…”
Section: Attention and The Mccollough Effectsupporting
confidence: 89%
“…It has also been suggested that attention is not required for the perception of the McCollough either. Thompson and Travis (1989), following earlier studies by Mayhew and Frisby (1978), showed that it took subjects several seconds to discriminate two textures, each composed of overlaid gratings with different orientations. If, however, the subjects were first exposed to an induction period in which each of the textures was colored red or green, respectively, then, after such induction, the two textures could be discriminated much more quickly.…”
Section: Attention and The Mccollough Effectmentioning
confidence: 90%
See 1 more Smart Citation
“…wavelength rather than perceived color, Thompson and Latchford, 1986;cf. also Houck and Hoffman, 1986;Humphrey, Gurnsey, and Fekete, 1991;Thompson and Travis, 1989;White, Petry, Riggs, and Miller, 1978), to describe contingent aftereffects as the classical conditioning of color and orientation, for example, is potentially very misleading --especially for those who are naive about visual processing.…”
Section: Classical Conditioning Accounts Of Adaptationmentioning
confidence: 99%
“…MacKay & MacKay, 1975;Savoy, 1984;and Vidyasagar, 1976, for evidence of dichoptic and binocular effects) and are specific to retinal orientation (Bedford & Reinke, 1993;Ellis, 1976), retinal size (Harris, 1970), and retinal color (i.e., wavelength, rather than perceived color; Thompson & Latchford, 1986). There is also evidence that conscious perceptual discriminability of the form stimuli is not critical to the effect (Humphrey, Gurnsey, & Fekete, 1991;Thompson & Travis, 1989). Indeed, the effect can be generated in patients who have severe cortical impairments of form and orientation perception with a sparing ofarea V 1 (Humphrey, Goodale, Corbetta, & Aglioti, 1995;Humphrey, Goodale, & Gurnsey, 1991), suggesting a locus in primary visual cortex (i.e., where McCollough, 1965, first proposed).…”
Section: Varieties Of Contingent Visual Aftereffectsmentioning
confidence: 99%